1996
DOI: 10.1108/08876049610106699
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived service quality and name familiarity on the service selection decision

Abstract: Traditional promotional programs have, in the main, concentrated on building brands. This is true whether the brand is a product or a company and the advertising expenditure involved is seen as an investment rather than a cost. Does this familiar construct hold true in service industries? Arora & Stoner's findings, albeit from a limited study, seem to support the assertion that branding is equally important for service companies and in some ways the intangibility of the service product would suggest that famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 14 publications
4
57
0
1
Order By: Relevance
“…While commenting on brand aroused feelings, Ghazizadeh et al strongly supported the previous research conducted by Richins, Boles et al, Arora et al ( [15], [22], [23], [24]). Richins believes that emotional variables like feelings is important in purchase decision making and plays an important role in effecting customers" reactions [22].…”
Section: Theoretical Linkage IIIsupporting
confidence: 76%
“…While commenting on brand aroused feelings, Ghazizadeh et al strongly supported the previous research conducted by Richins, Boles et al, Arora et al ( [15], [22], [23], [24]). Richins believes that emotional variables like feelings is important in purchase decision making and plays an important role in effecting customers" reactions [22].…”
Section: Theoretical Linkage IIIsupporting
confidence: 76%
“…37 Perceived service quality has a signifi cant effect on the attitude towards obtaining insurance. 38 Moreover, the degree of success in the implementation of enterprise mobilization in the life insurance industry is positively correlated to the management performance of external aspects like providing increased customer satisfaction. 39 It has been observed that insurance agents should constantly monitor the level of satisfaction among his / her customers to keep themselves close to the customers for fulfi lling their needs.…”
Section: Indian Life Insurance Sectormentioning
confidence: 99%
“…Functional quality could be explicated as a perception of the way in which a service was provided; it defines a customer's perception of interaction that takes place during the service provision process and relates to the satisfaction that the service recipient feels toward the process or experience of receiving the service (Arora and Stoner, 1996). On the other hand, technical quality reflects the result of the service action, service output or what the customer received after the service encounter.…”
Section: Functional and Technical Service Qualitymentioning
confidence: 99%